Digital Storytelling as a Media for Health Promotion in School Children - Syarifah Nazifah; Sigit Mulyono (Jurnal Keperawatan Silampari, 2023)
This research aims to determine digital storytelling as a health promotion medium for school children. The research method used in this study was a systematic review taken from Science Direct, Scopus, Proquest, Sage Journal, and Clinical Key search engines, which were filtered in title, abstract, and complete studies. All journal articles, including experimental, mixed methods, randomized controlled trials, and qualitative analyses, are in English. The research results showed that seven articles were included in the review. Research has been conducted in health promotion with different digital storytelling processes. The results of this review show that digital storytelling increases knowledge, perception, motivation, and social support. In conclusion, this systematic review shows that digital storytelling interventions positively influence health promotion, especially at school age. Keywords: Digital Storytelling, Health Promotion, School Age